2000
DOI: 10.1002/(sici)1097-4628(20000118)75:3<452::aid-app16>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Urea-induced conformational changes of chitosan molecules and the shift of break point of Mark-Houwink equation by increasing urea concentration

Abstract: Chitosan solutions of the same 83% degree of deacetylation (DD) but different weight average molecular weights (M w s) (78 -914 kDa) in 0.01M HCl containing different concentrations of urea (0 -6M) were prepared. Intrinsic viscosity ([]) and weight average molecular weight (M w ) of chitosan were measured with a capillary viscometer and light scattering, respectively. Mark-Houwink exponent a was used as the parameter of conformational index. The Mark-Houwink exponent a increased with increasing concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[35,36] Few studies report the effects of urea on the hydrodynamic behavior of chitosan in solutions; Gamzazade et al [37] and Sklyar et al [38] showed that the intrinsic viscosity of chitosan solutions increased in the presence of 8 mol Á L À1 urea. Similarly, Chen and Tsaih [39,40] demonstrated increased intrinsic viscosity of chitosan in solutions containing urea compared to chitosan solutions without urea. The authors hypothesized that an extended conformation of the chitosan chains results from disruption of intra-and intermolecular hydrogen bonds in the polymer caused by urea.…”
Section: Effect Of Urea On Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,36] Few studies report the effects of urea on the hydrodynamic behavior of chitosan in solutions; Gamzazade et al [37] and Sklyar et al [38] showed that the intrinsic viscosity of chitosan solutions increased in the presence of 8 mol Á L À1 urea. Similarly, Chen and Tsaih [39,40] demonstrated increased intrinsic viscosity of chitosan in solutions containing urea compared to chitosan solutions without urea. The authors hypothesized that an extended conformation of the chitosan chains results from disruption of intra-and intermolecular hydrogen bonds in the polymer caused by urea.…”
Section: Effect Of Urea On Chitosanmentioning
confidence: 99%
“…The viscosity of chitosan in solutions containing 8 mol Á L À1 urea is higher than in urea-free aqueous solutions for the same pH, in good agreement with previous viscometric studies. [37][38][39][40] This effect is probably due to the specific association between macromolecules of chitosan and urea, presumably, via hydrogen bonding. In fact, urea acts as a co-solvent and provides additional solvation to the macromolecules of chitosan, in agreement with the IR results discussed above.…”
Section: Hydrodynamic Behavior Of Chitosans At Different Phmentioning
confidence: 99%
“…4) -C-O-C-of the OXE ring, which undergo bond cleavages when the OXE-CHI-PUR network is mechanically damaged and exposed to UV radiation. These processes generate reactive free radicals (b1, b2, and b3) and a carbocation (b4) during the self-repairing process, where the OXE ring opening reaction (b4) propagates cationically, [3][4][5]18,19 but -NHCONH-(PUA) and -C-O-C-bond cleavage generate free radicals (b2). 1,11,12 On the other hand, close packing and/or network shrinkage upon UV exposure due to chair-to-boat conformational changes (Fig.…”
Section: Cationic Vs Free Radical Processesmentioning
confidence: 99%
“…Several have been focusing on the investigation of the physical properties of dilute solutions (Anthonsen, Vårum, & Smidstrød, 1993;Chen & Tsaih, 2000;Tsaih & Chen, 1997;Wetton, Marsh, & Ven-de-Velde, 1991) looking at the effect of pH, ionic strength, DDA and molecular weight on the conformation of the chitosan molecule. Other studies have dealt with the rheological properties of concentrated chitosan solutions (Desbrières, 2002;Mucha, 1997;Nystrom, Kjøniksen, & Iversen, 1999;Wang & Xu, 1994).…”
Section: Introductionmentioning
confidence: 99%